Invisible Mothers: Unseen yet Hypervisible After Incarceration. By Garcia-HallettJanet (University of California Press, 2022, 248pp. £30.00) - Michalsen, Venezia (The British Journal of Criminology, 2023)
Invisible Mothers: Unseen yet Hypervisible After Incarceration, the new book by Dr. Janet Garcia-Hallett, has almost innumerable contributions to the field. The first thing that the reader will likely notice that makes this work stand out is the impact of Garcia-Hallett’s positionality as an Afro-Latina mother on the holistic understanding of the experiences of the Black and brown women as mothers and victims of the racist American carceral system. Garcia-Hallett grew up in Harlem, witnessing the transformation of her community due to the takeover of the penal system. For this book, she interviewed 37 mothers in New York City with histories of incarceration, and her writing skilfully puts the reader in her shoes as she presents the findings from her interviews, which took place in their kitchens, booths in McDonald’s, and at tables in shelters. In her exploration of these women’s experiences, Garcia-Hallett departs from the traditional pitiful exploration of their lives, but instead, paints a complicated, multifaceted picture of women engaging actively in many different types of motherwork, while facing almost constant obstacles from racist and misogynist criminal legal and child welfare systems that criminalize, pathologize and penalize their survival of their marginalization, rather than helping ‘save’ children and their mothers. She provides a critical and structural analysis while also introducing each woman as deeply unique in her strengths and challenges and is able to acknowledge the importance of the children without letting them overshadow the mothers. This is no small feat.
Keywords: book.review; dept.soc

Organizational scaffolding for climate adaptation: how intermediaries manage evaluative tensions - Wissman, Nichole Kay; Bertana, Amanda; Manning, Stephan Davys (Academy of Management Proceedings, 2023)
The grand challenge of preparing for climate impacts through climate adaptation relies on intermediaries, including local NGOs, consulting firms, and government agencies. Climate adaptation elicits evaluative tensions coming from what we call the dual organizational complexity. The dual organizational complexity includes evaluation ambiguity in (1) the interconnectedness and co-evolutionary dynamics of locally bounded social and ecological systems and (2) an increasingly complex network of interconnected organizations, including a diverse set of public, private, and semi-private actors who provide funding, market power, and expertise. We find that intermediaries address evaluative tensions through organizational scaffolding or building socio-material infrastructures that can support resilience and increase evaluative and adaptive capacity for future projects, albeit imperfectly. Importantly, we argue that climate adaptation needs facilitators with the capacity to connect very localized bottom-up needs to top-down resources in a continuous cycle of resource allocation, communication, and accountability, especially in the face of the increasing organizational complexity involved.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizations and the Natural Environment; dept.soc

Breaking wind: A comparison between U.S. and European approaches in offshore wind energy leadership in the North Atlantic region - Gallaher, Adam; Graziano, Marcello; Axon, Stephen; Bertana, Amanda (Renewable and Sustainable Energy Reviews, 2023)
The United States has only recently begun investing in commercial-scale offshore wind energy (OWE). Although the United States is slow to progress, it is uniquely positioned to build on the existing knowledge that coastal European countries have applied for their own energy transitions. In this study, we analyze how federal and regional plans for expanding the OWE sector in the United States brought to the surface decade-long tensions related to multi-scale governance mismatches, jurisdictional conflicts, and unclear pathways for implementing national industrial policies. Drawing upon the European experience with OWE, we employ a dynamic multi-level perspective framework enriched by socio-ecological elements to examine the United States energy transition through its most promising technology. From our framework we identify six categories of OWE developments characterized by both unique and shared elements between the United States and European coastal countries. These elements are: (1) role of local communities, (2) governance structures, (3) multi-scale government interactions, (4) regional socioeconomic structures, (5) socio-ecological impacts, and (6) relationships with existing industries. Drawing upon our analysis, we identify and conceptually map four research areas in need of further development for the United States and the research community— (1) knowledge, (2) potential, (3) adaptation, and (4) learning. These insights provide critical information to ensure that the United States expansion into offshore energy generation is characterized by elements of justice, equity, and inclusive regional economic development.
0 citations (Crossref) [2023-10-31]
Keywords: Blue economy; Comparative analysis; Just energy transitions; Multi-level perspective; Offshore wind energy; dept.egm; dept.soc; peer-reviewed

Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Education - Meyerhoffer, Cassi A.; Rodriguez, Brittany Leigh (University of Georgia Press, 2023)
Over the last several years, the United States has experienced a surge in bystander videos that have captured incidents of police brutality and prejudice directed largely at Black people. Public outrage surrounding police brutality persists as these incidents continue to reach the public eye. As public discourse around police brutality and racial inequality largely centers on specific events, there is a dearth of information about systemic racism and how race and racism pervade every single aspect of American life. How Black people are often treated by law enforcement is reflective of larger historical racial inequities and injustices that extend far beyond the criminal justice system and intersect with how Black people access housing, occupy public spaces, and are treated in American public schools.Imprisoned: Interlocking Oppression in Law Enforcement, Housing, and Public Educationfocuses on contemporary systemic racism as it relates to how the U.S. criminal justice system, housing system, and education system intersect to create a matrix of inequality for Black people. To illustrate the systemic nature of racism in American policing and communities, this book highlights contemporary policies and practices that intersect with residential segregation and public schooling that continue to affect Black people on a large-scale, structural level―demonstrating the extent to which the United States criminal justice system is tied to where people live and how they are treated and educated in public schools.
Keywords: dept.soc